2021
DOI: 10.1093/jscr/rjab350
|View full text |Cite
|
Sign up to set email alerts
|

Safe laparoscopic resection of a giant schwannoma in the retroperitoneum using a fluorescent ureteral stent: a case report

Abstract: Schwannomas that occur in the retroperitoneal cavity are rare. We herein report a patient who underwent safe laparoscopic resection by using a preoperative 3D computed tomography (CT) image and a fluorescent ureteral stent during the surgery. A 47-year-old man presented with left lower abdominal pain. CT showed a 10-cm continuous retroperitoneal tumor originating at the third lumbar nerve in the lower left abdomen. Schwannoma was suspected. We underwent laparoscopic resection of the tumor guided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…It has been reported that prophylactic placement of double-J tube is widely used in pelvic floor surgery (Urology, Anorectum, and Gynecology), which can better expose the ureter and reduce the risk of ureteral injury. [ 19 , 25 , 26 ] Thus, it is recommended that double-J tubes be placed prophylactically before the operation to improve the surgical effect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that prophylactic placement of double-J tube is widely used in pelvic floor surgery (Urology, Anorectum, and Gynecology), which can better expose the ureter and reduce the risk of ureteral injury. [ 19 , 25 , 26 ] Thus, it is recommended that double-J tubes be placed prophylactically before the operation to improve the surgical effect.…”
Section: Discussionmentioning
confidence: 99%
“…In our cases, preoperative MR revealed that the tumor was near the ureter in this case, which was confirmed by intraoperative observation. Therefore, combined with the experience of pelvic surgery in urology, Anorectum and Gynecology, [ 19 , 25 , 26 ] laparoscopic resection combined with catheter placement under cystoscope was chosen. Before laparoscopy, the double-J catheter was placed in the ureter with a cystoscope.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations